PENERAPAN METODE PEMBELAJARAN EKSPERIMEN UNTUK MENINGKATKAN KETELITIAN DAN PRESTASI BELAJAR ( Studi Pada Muatan Pelajaran IPA Siswa Kelas IV di SD Negeri Kecamatan Pagar Alam Utara Kota Pagar Alam ) - Muslim Amrullah (UNIB Press, 2021)
The purpose of this study (1) Application of experimental learning methods to increase the accuracy of student learning science subject content fourth grade student at SD Negeri Pagar Alam sub-district Pagar Alam City. (2) The application of experimentallearning methods in improving student achievement in science subject content of grade IV student in SD Negeri Pagar Alam sub-district City of Pagar Alam. (3) Effectiveness application of experimental learning methods when compared with convensional learning methods. Population in the study are grade IV students of SD Negeri 46 Pagar Alam and grade IV students SD Negeri 12 Pagar Alam, amounting to 66 people. Instrument peoplethis study uses an abservation sheetand test. Research data analyzed bydescriptive statistics, persentageand test, research resultshows that the application of the experimental learning method canimprove the accuracy and learningachievement of fourth gradestudent of SD Negeri in Nort Pagar Alam District